Novel De Novo Intronic Variant of SYNGAP1 Associated With the Neurodevelopmental Disorders - Wuming Xie; Baoqiong Liao; Mei Shuai; Rutian Liu; Min Hong; Shuwen He (Molecular Genetics & Genomic Medicine)
ABSTRACT Background SYNGAP1 encodes a Ras/Rap GTPase‐activating protein that is predominantly expressed in the brain with the functional roles in regulating synaptic plasticity, spine morphogenesis, and cognition function. Pathogenic variants in SYNGAP1 have been associated with a spectrum of neurodevelopmental disorders characterized by developmental delays, intellectual disabilities, epilepsy, hypotonia, and the features of autism spectrum disorder. The aim of this study was to identify a novel SYNGAP1 gene variant linked to neurodevelopmental disorders and to evaluate the pathogenicity of the detected variant. Methods A novel de novo intronic variant in SYNGAP1 was identified by Whole exome sequencing (WES) and confirmed by Sanger sequencing. Minigene assays were conducted to assess whether the intronic variant in SYNGAP1 influenced the normal splicing of mRNA. Results A novel de novo intronic variant in SYNGAP1 (c.3582+2T>G) was indentified with clinical features suggestive of neurodevelopmental related disorders. Minigene splicing analysis demonstrated that this noncanonical splice site variant led to the activation of a cryptic acceptor splice site. Consequently, 101 base pairs of intron 16 were aberrantly retained in the mRNA, leading to a frameshift. This frameshift resulted in the introduction of a premature stop codon (TGA) in the coding sequence and the production of a truncated SYNGAP1 protein, potentially leding to loss of function and subsequent disruption of its biological roles. Conclusion Our findings highlight the significance of de novo pathogenic SYNGAP1 variants at the intron 16/exon 17 junction in the SYNGAP1‐related neurodevelopmental disorders, providing novel insights into the genetic basis and diagnosis of these disabilities.